2012
DOI: 10.1007/s10661-012-2609-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface geophysical exploration: developing noninvasive tools to monitor past leaks around Hanford’s tank farms

Abstract: A characterization program has been developed at Hanford to image past leaks in and around the underground storage tank facilities. The program is based on electrical resistivity, a geophysical technique that maps the distribution of electrical properties of the subsurface. The method was shown to be immediately successful in open areas devoid of underground metallic infrastructure, due to the large contrast in material properties between the highly saline waste and the dry sandy host environment. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The scale at which the LE‐ERT method can be applied has been demonstrated clearly at the pilot scale (scale = X) and the environmental site characterization scale (scale = 100X). For example, Rucker et al (2012b) mentioned surveys where the site was on the order of 100 ha and the target was as at least 70 m below ground surface, which is approximately two orders of magnitude larger in scale than presented here. The small to intermediate reservoir scale (1000X) also should easily be accommodated as long as a sufficient density of wells exist to the depth of the target, as shown in Daily et al (2004).…”
Section: Reservoir Considerationsmentioning
confidence: 76%
See 1 more Smart Citation
“…The scale at which the LE‐ERT method can be applied has been demonstrated clearly at the pilot scale (scale = X) and the environmental site characterization scale (scale = 100X). For example, Rucker et al (2012b) mentioned surveys where the site was on the order of 100 ha and the target was as at least 70 m below ground surface, which is approximately two orders of magnitude larger in scale than presented here. The small to intermediate reservoir scale (1000X) also should easily be accommodated as long as a sufficient density of wells exist to the depth of the target, as shown in Daily et al (2004).…”
Section: Reservoir Considerationsmentioning
confidence: 76%
“…Although much of the past focus has been on ensuring that targets can be reproduced, little effort has been spent increasing the utility and enhancing the resolution of the long electrode method. Rucker et al (2012b) demonstrated that combining long electrodes with short electrodes on the surface can distinguish between shallow and deep targets, but a large number of electrodes are needed on the surface and around the perimeter of the survey area to be effective. Zhu & Feng (2011) also demonstrated that a large number of short electrodes on the surface, combined with a single long electrode in the centre of the survey area, could be used to determine the proper depth of a pair of relatively shallow targets.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot‐scale validation experiment was conducted to test the ability of the long‐electrode electrical resistivity tomography method to reconstruct a known target. The scale of the validation test was on the order of 1/17 of a typical Hanford nuclear waste tank, where the long electrode electrical resistivity tomography (LE‐ERT) method was applied to image several waste plumes that have developed beneath the tanks from accidental releases (e.g., Rucker et al . 2010, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…From a modelling perspective, the larger cell size actually created the highest model resolution values, with the lowest resolution observed from the model with no depth electrodes. Depth electrodes are important when surface electrodes are sparse and arrays of depth electrodes buried in actual tank farm settings have proven to be a valuable means to evaluate historical leaks (Rucker et al . 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation